The Effect of Inflation on Domestic Migrant Worker Households in China - Zhang, Shishu (Journal of Reviews on Global Economics, 2013)
Domestic migration workers and inflation are two phenomena attracting attention from worldwide scholars. The article endeavors to accomplish the following three tasks: a) describe the characteristics of inflation and immigration situations in China; b) study the effect of inflation on domestic immigrants' the expenditures; c) understand the effect of inflation on immigrants' happiness and satisfaction. The paper found out that in all the eight expenditure categories, only three categories (food, clothing and housing) are negatively affected by inflation. Other five expenditure categories (health and medical, house equipment, facilities and services, entertainment, educational and cultural activities, transportation and communication, tuition, and miscellaneous) are positively affected by inflation. The biggest reduction of expenditure is in transportation and communication with a coefficient of -0.025. The paper also found out that the lower income group's expenditure is more affected by inflation then higher income group. The paper showed that inflation didn't have a significant effect on people's feeling of happiness and their satisfaction.